17-year elevated temperature study of HDPE geomembrane longevity in air, water and leachate. Issue 5 (24th September 2018) - Ewais, A. M. R.; Rowe, R. K.; Rimal, S.; Sangam, H. P.
Abstract : A 17-year investigation of a geomembrane (GMB) aged at 55, 70 and 85°C in air, water and leachate is reported. At test termination, the mechanical properties had only reached nominal failure in leachate and water at 70 and 85°C. Consistent with a previous study, there is a significant reduction in stress crack resistance (SCR) before there is clear evidence of oxidative degradation; this is attributed to the morphological changes due to disentanglement of entangled polymer chains. The effect of this apparent morphological change on SCR appeared to be greatest for the GMB when immersed in water and leachate at 70°C, although it is evident for all fluids at all three test temperatures. Using the most conservative estimates, the time to nominal failure ( t NF, time to 50% of the initial or specified property value) in leachate, water and air (no UV exposure) ranged from >13, 18 and 170 years at 60°C to 660, 1500, and 1700 years, respectively, at 20°C. Assuming minimal tensile strains in the GMB, the time to nominal failure of this GMB in a composite liner is likely estimated to vary from >50 years at 60°C to >550 years at 35°C and > 1100 years at 20°C.